2018
DOI: 10.1039/c8nh00135a
|View full text |Cite
|
Sign up to set email alerts
|

Au3Cu tetrapod nanocrystals: highly efficient and metabolizable multimodality imaging-guided NIR-II photothermal agents

Abstract: Au3Cu tetrapod nanocrystals were synthesized. After surface modification, the obtained monodisperse Au3Cu@PEG-Cy5,FA showed great potential as a fluorescence imaging and MSOT imaging-guided photothermal agent in the NIR-II region, which could be metabolized in vitro after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 55 publications
0
27
0
Order By: Relevance
“…e) Calculation of the photothermal conversion efficiency at 1064 nm. f) Comparison of photothermal conversion efficiency (η) of reported PTT agents in the NIR‐II biowindow: 1) AuNCs@SiO 2 ; 2) Au 3 Cu@PEG TPNCs; [ 46 ] 3) Au‐wires‐on‐AuNR; [ 47 ] 4) Pt Spiral; [ 48 ] 5) Cu 2 MnS 2 NPs; [ 49 ] 6) Nb 2 C (Mxene); [ 50 ] 7) Cu 3 BiS 3 NRs; [ 51 ] 8) L‐Pdots; [ 52 ] 9) TBDOPV‐DT NPs; [ 53 ] 10) SPN‐DT. [ 54 ] g) Relative viabilities of 4T1 cells after co‐incubation with different concentrations of AuNCs@SiO 2 under different 1064 nm laser treatment (0.5 W cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…e) Calculation of the photothermal conversion efficiency at 1064 nm. f) Comparison of photothermal conversion efficiency (η) of reported PTT agents in the NIR‐II biowindow: 1) AuNCs@SiO 2 ; 2) Au 3 Cu@PEG TPNCs; [ 46 ] 3) Au‐wires‐on‐AuNR; [ 47 ] 4) Pt Spiral; [ 48 ] 5) Cu 2 MnS 2 NPs; [ 49 ] 6) Nb 2 C (Mxene); [ 50 ] 7) Cu 3 BiS 3 NRs; [ 51 ] 8) L‐Pdots; [ 52 ] 9) TBDOPV‐DT NPs; [ 53 ] 10) SPN‐DT. [ 54 ] g) Relative viabilities of 4T1 cells after co‐incubation with different concentrations of AuNCs@SiO 2 under different 1064 nm laser treatment (0.5 W cm −2 ).…”
Section: Methodsmentioning
confidence: 99%
“…For example, the hypoxia tumor microenvironment (TME) deteriorates the PDT efficiency and the heat shock response weakens the PTT effect. [16][17][18][19][20][21][22][23][24][25][26] As an emerging therapeutic strategy, the fundamental mechanism of chemodynamic therapy (CDT) involves the generation of highly toxic hydroxyl radicals (•OH) from endogenous hydrogen peroxide (H 2 O 2 ) catalyzed by transition metal, metal, or peroxidase-like catalysts through in situ treatment. [27][28][29][30][31][32][33][34] If the Fenton or Fenton-like reactions can simultaneously produce oxygen (O 2 ) along with •OH, the generated O 2 may also relieve TME hypoxia and enhance the therapeutic efficacy of PDT simultaneously.…”
mentioning
confidence: 99%
“…Subsequently, we further evaluated the nanozyme activity of Ag 2 S@Fe 2 CDSPE PEGiRGD in cancer cells. Because nonfluorescent dihydrorhodamine 123 (DHR123) can be oxidized by ROS into green fluorescent rhodamine 123, DHR123 was used as an intracellular ROS indicator (36). Fortunately, the strongest fluorescence intensity was shown in the group of Ag 2 S@Fe 2 CDSPEPEGiRGD under the ir radiation of 808nm laser, which demonstrated that the nanozyme (Fig.…”
Section: Evaluation Of Enhanced Cellular Uptake Ros-generation and mentioning
confidence: 95%